PEMBERDAYAAN GURU MELALUI PROGRAM PELATIHAN DETEKSI DINI TUMBUH KEMBANG ANAK DIDIK - Nuzuliana, Rosmita; Ratnaningsih, Sri (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
Reducing stunting rates in Indonesia is the responsibility of all sectors, including the early childhood education sector. This program is an additional burden for early childhood education  teachers because the implementation of the program is evaluated directly during the institution's accreditation activities. The problem that occurs is the teachers, especially those who are members of the Aisyiyah Bustanul Athfal (IGABA) teachers' association in Turi Sleman, are not health workers and not all teachers have been exposed to training related to growth and development detection. The results of the identification, 95% of teachers have not been exposed at all to how to detect growth and development. For this reason, we help the community, especially teachers, to be able to detect growth and development for students by providing training to IGABA’s teachers on child growth and development detection. The total implementation of the activity was carried out for one month starting from preparation, implementation and evaluation. Preparations were made starting from coordination, equipment preparation. The implementation of activities using educational methods through lectures and discussions, demonstrations, roleplay. Evaluation was carried out after the action to determine the level of knowledge and skills after training. Participants who took part in this activity were 35 IGABA teachers from 8 schools. The results found that there was an increase in teacher knowledge and skills in detecting child growth and development. The average increase in knowledge was 24.4 and the average difference in skill scores before and after was 48.086. These good results are expected to enable teachers to routinely implement detection of student growth and development so that they can help implement government programs. In addition, we provide a module book in monitoring student growth and development entitled Jejak Tumbuhku and a set of educational game tools for growth and development detection in each school for the implementation of growth and development detection in each school.